Electrical characterisation of commercial optoelectronics diodes and quantum dot based diodes subjected to neutron radiation - Dhiyauddin Ahmad Fauzi (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Owing to its ability to manipulate light, optoelectronics diodes have extensively been used in many applications including in radiation harsh environment systems where constant exposure to various types of radiation damages such as the displacement damage is inevitable. Therefore, knowledge on the degradation of these components is highly important as to provide insight for future device and simulation databases development. This work presents the effects of neutron radiation on the current-voltage (I-V) and capacitance-voltage (C-V) characteristics of selected commercial gallium arsenide (GaAs) infrared emitting diodes (IREDs), gallium nitride on silicon carbide (GaN/SiC) light emitting diodes (LEDs), silicon (Si) photodiodes, InAs/GaAs and InAs/InAlAs novel quantum dot-in-a-well diodes (DWELL). Studies were conducted by exposing all diodes to neutron radiation ranging from 3.0×1013 to 1.08×1015 neutron/cm2 via pneumatic transfer system (PTS) in PUSPATI TRIGA Mark II research reactor, Malaysian Nuclear Agency. After neutron irradiation of 3.0×1013 n/cm2, the forward-bias I-V characteristics of the InAs/GaAs DWELL sample show an increase in the leakage current up to 3 orders of magnitude and series resistance by 0.03Ω. The capacitance in the C-V characteristics after irradiation however decreases which implies the decrease in the corresponding doping concentration. This is believed to be attributed to two major processes; carrier removal due to deep carrier trapping, indicated by the reduction in the effective doping concentration by a maximum of 41% and neutron transmutation doping (NTD) effect indicated by the formation of germanium (Ge) and selenium (Se) isotopes on the gallium (Ga) and arsenic (As) sites. Further in-depth study was conducted via temperature-dependence measurement where the reverse-bias mechanism of the DWELL samples were derived and found to be largely due to the trap-assisted generation-recombination (TAGR) and Frenkel-Poole (F-P) process. Hence, this implies that the neutron radiation do not alter the carrier transport mechanism of the DWELL samples, instead, it increases the trap densities and decreases the C-V values. As for the I-V characteristics of the commercial samples, the GaAs IREDs exhibit an increase in the leakage current, while the GaN LEDs show an unchanged behavior even when irradiated with the highest fluence level. In conclusion, radiation induced damage causes no changes in carrier dynamics inside a DWELL structure and that the GaN based sample is the most radiation tolerant compared to other tested samples.